Years of Life Lost Attributable to Estimated Air PM Using High-Resolution Satellite Data in a Region of Iran - Samira Soleimani; Omid Aboubakri; Afshin Maleki; Reza Rezaee; Serveh Fathi; Mahdi Safari; Shoboo Rahmati (Environmental Health Insights)
In this study, we aimed to investigate the impact of predicted particulates with a diameter of 2.5 μm or less (PM 2.5 ) using the satellite data on Years of Life Lost (YLL) as a health burden of air pollution. A 2-stage methodology was used in order to predict PM 2.5 using Aerosol Optical Depth (AOD). The predicted PM was corrected for its bias through Bland-Altman method and observed data. Relative Risk (RR), Attributable Fraction (AF), and Attributable Number (AN) of YLL were estimated as the effect of PM 2.5 on health. Based on the minimum value as the optimum value of PM, statistically a significant cumulative dose-response association was found. The significant association was mainly observed between lags 4 and 13. Also, based on the scenario, the total estimated YLL attributable to air pollution was 74227 years, with an AF of 0.45 which was statistically significant (95% CI: 0.14, 0.65). Based on the median value as the second scenario, there was not cumulative significant dose-response association. The subgroup analysis revealed that females and the elderly exhibited higher PM 2.5 -related YLL compared to males and younger, respectively. Totally, the study revealed that impact of the predicted PM on YLL was significant when we selected the minimum value as reference. While, the impact was insignificant when we changed it to median value. This result highlights the important effect of reference value selection on the interpretation of dose-response and lag-response associations between PM 2.5 and YLL which should be addressed in next studies.